The Efficacy of Early Mobilization after Urologic Radical Surgery - ÇAM, HAYDAR KAMİL (GALENOS YAYINCILIK, 2015)
Contemporary evidence based trials suggest that same changes in the traditional approach for the care of patients provide a rapid recovery and return to daily life after surgery. Consequently, a decrease in the surgical complications and shorter hospital stay would be provided. These new multi-perspective approaches which are different from the classical approach are defined as fast track surgery. Early mobilization besides early extubation and rapid discharge from extensive care unit constitute the major components of fast track surgery in order to bring a shorter hospital stay. Nurses together with surgeons and anesthesiologists are all active members of the care team which may also include the patient by him or herself. The aim of this review was to discuss the efficacy of early mobilization after urologic surgeries.
Keywords: Early mobilization; radical surgery; urologic surgery